Effect of preoperative gabapentin on pain intensity and development of chronic pain after carpal tunnel syndrome surgical treatment in women: randomized, double-blind, placebo-controlled study - Sadatsune, Eduardo Jun [UNIFESP] (2016)
CONTEXT AND OBJECTIVES: Effective postoperative analgesia is important for reducing the incidence of chronic pain. This study evaluated the effect of preoperative gabapentin on postoperative analgesia and the incidence of chronic pain among patients undergoing carpal tunnel syndrome surgical treatment. DESIGN AND SETTINGS: Randomized, double-blind controlled trial, Federal University of Sao Paulo Pain Clinic. METHODS: Forty patients aged 18 years or over were randomized into two groups: Gabapentin Group received 600 mg of gabapentin preoperatively, one hour prior to surgery, and Control Group received placebo. All the patients received intravenous regional anesthesia comprising 1% lidocaine. Midazolam was used for sedation if needed. Paracetamol was administered for postoperative analgesia as needed. Codeine was used additionally if the paracetamol was insufficient. The following were evaluated: postoperative pain intensity (over a six-month period), incidence of postoperative neuropathic pain (over a six-month period), need for intraoperative sedation, and use of postoperative paracetamol and codeine. The presence of neuropathic pain was established using the DN4 (Douleur Neuropathique 4) questionnaire. Complex regional pain syndrome was diagnosed using the Budapest questionnaire. RESULTS: No differences in the need for sedation, control over postoperative pain or incidence of chronic pain syndromes (neuropathic or complex regional pain syndrome) were observed. No differences in postoperative paracetamol and codeine consumption were observed. CONCLUSIONS: Preoperative gabapentin (600 mg) did not improve postoperative pain control, and did not reduce the incidence of chronic pain among patients undergoing carpal tunnel syndrome surgery.